Noncognitive Skills, School Achievements and Educational Dropout (Revised Version) - Katja Coneus; Johannes Gernandt; Marianne Saam (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We analyse the determinants of dropout from secondary and vocational education in Germany using data from the Socio-Economic Panel from 2000 to 2007. In addition to the role of classical variables like family background and school achievements, we examine the effect of noncognitive skills. Both, better school grades and higher noncognitive skills reduce the risk of becoming an educational dropout. The influence of school achievements on the dropout probability tends to decrease and the influence of noncognitive skills tends to increase with age.
Keywords: I21; J13; J24; 330; Noncognitive skills; school grades; secondary education; vocational training; Abbrecher; Kognition; Allgemeinbildende Schule; Berufsbildung; Bildungsniveau; Bildungsertrag; Deutschland